Elastic modulus of the amorphous phase confined between lamellae: The role of crystalline component. (13th March 2023) - Polinska, Malgorzata; Rozanski, Artur; Kozanecki, Marcin; Galeski, Andrzej
Abstract: The correlation between the modulus of the interlamellar amorphous phase and the microstructure of the crystalline component was studied. The experimental method involving deformation of the amorphous layers only developed by us was used. Three polyethylenes with different architecture of macromolecules and thermal history were analyzed. In the case of HDPE and low density polyethylene (LDPE), a practically linear increase of the elastic modulus of the confined amorphous phase with the increase of the crystal thickness (in the range of ≈4–20 nm) was observed and explained by activation of α relaxation process in crystalline lamellae. For thin crystals the degree of activation of the α relaxation was intense and the influence of crystalline component on the modulus of amorphous regions was the lowest. For materials with thick crystals the degree of activation of the α relaxation was lower and the "confining" influence of crystalline component on the amorphous phase was the highest. In ethylene-octane copolymer (EOC) materials with the thinnest crystals (≈2–3 nm) the modulus of the confined amorphous phase was close to the modulus of the bulk amorphous phase-in those materials the α relaxation process was not observed at all. The modulus of the amorphous phase of isothermally crystallized HDPE (≈70 MPa) was over twenty times higher than the modulus of the bulk amorphous phase (≈3 MPa). Graphical abstract: Image 1 Highlights: Three polyethylenes ( PEs ) with different thickness of crystals ( l c ) were analyzed. The modulus of the interlamellar amorphous phase ( E a ) of PEs were determined. Linear increase of E a with the increase of l c was observed. E a .→ l c was correlated with the α relaxation process activated in crystalline lamellae.